Storie di Terracotta 1: International Conference. What Can Terracottas Tell Us: Coroplastic Polysemy in the Ancient Mediterranean. Cagliari, Cittadella dei Musei 10–12th November 2022 - Romina Carboni; Claudia Cenci; Nicola Chiarenza (Les Carnets de l’ACoSt)
This conference was planned as the first in a series of scholarly events dedicated to the study of votives, with a special focus on the role of figurative terracottas in the ancient Mediterranean. These highly versatile artifacts had a polysemic value that was manifested relatively directly by the formal language used, by their contexts of discovery, and by their association with other votive objects.